Empreendedorismo social: uma abordagem sobre a questão de gênero no Brasil - Cruz, Renata da Conceição (2007)
Nowadays, themes like third sector, volunteerism, and social entrepreneurship are highlighted for they are social problems yet to be dealt with by the state. Based on this context, social entrepreneurship, a relatively new concept, arises as a new form of private entrepreneurship but with some differences regarding their objectives: stop seeking personal profit in order to seek solutions for problems from communities, social groups and from specific areas such as health, environment and education, among others. This research aimed at the analysis of this new form of entrepreneurship focusing on the genre issues of the social environment. Initially, it was done a bibliographical research on topics like third sector, volunteerism, social entrepreneurship and genre, this research intended to create a theoretical base for the discussion of such theme. Later a qualitative and quantitative research was done with a sample of social entrepreneurs which resulted on thirty surveys answered in three private interviews. The thesis that social entrepreneurs had already been in the private entrepreneurship has proven to be incorrect. Nonetheless the thesis that these entrepreneurs had above average income and a high instruction level, which allowed them to deal with social issues since their basic needs had been taken care of, has proven to be true. The results have showed also that entrepreneurs from both genres acknowledge the competition in the social sector, and over half of the sample believes that there is a genre competition in the sector. Furthermore, it has been observed that there is a higher concentration of women in the education and health areas and men in economic development and environment areas. However such conclusions can be broadened by the development of new researches